Incidence of extended spectrum beta-lactamase (ESBL) producing Escherichia coli isolated from women with urinary tract infections in Jordan - Rania Al-Groom (Iranian Journal of Microbiology)
Background and Objectives: Urinary tract infections are one of the world's major health problems. In addition, clinical disorders may result from the presence of bacteria or fungi in urine. The aim of this study was to isolate Escherichia coli (E. coli) strains from midstream urine samples, and to determine molecular characterization of encoded Extended Spectrum Beta-Lactamase (ESBL) genes. Materials and Methods: Collected urine samples were streaked on MacConkey, blood and EMB agar plates, then identifying E. coli isolates by using antibiotic susceptibility tests. ESBL production was measured using double disc diffusion. Furthermore, uniplex PCR was performed to identify two ESBL genes (blaCTX and blaTEM). Results: Among 412 isolates, 198 (48.1%) were E. coli strains, followed by Staphylococcus saprophyticus, Klebsiella sp., Serratia sp., Enterococci sp. and Proteus sp. with frequency of 132 (32.0%), 51 (12.4%), 15 (3.6%), 10 (2.4%), and 6 (1.5%) respectively. Female participants who were between the ages of 40 and 49 years old, married, and pregnant were more likely to develop urinary tract infections (UTIs). E. coli species were present in 189 (95.5) of the recurrent UTIs. Regarding antimicrobial susceptibility testing of E. coli isolates, the highest percentage of resistance and susceptible rates were found for nalidixic acid (75.8%) and gentamicin (64.1%) respectively. Among the E. coli isolates, 25 (12.6%) were ESBL-producers. The blaCTX-M gene was genetically confirmed in 20 (10.1%) of the isolates. Conclusion: E. coli is the most common cause of UTI and ESBL production leads to increased resistance to common antibiotics and complicates treatment strategies.